2004
DOI: 10.1093/ps/83.6.860
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Digestibilities and Divergent Selection for Digestion Ability in Growing Chicks Fed a Wheat Diet

Abstract: The genetic parameters of digestibilities for a wheat-based diet were estimated on 864 broilers. Two divergent lines (D+ and D-) were developed based on AMEn. The Rialto wheat variety was used as it is known to result in low digestibility values. Digestibility of lipids (DL), starch (DS), and proteins (DP) were measured individually using Near Infrared (NIR) analysis of freeze-dried excreta. Body weight, feed consumption (FC), feed conversion ratio (FCR) and residual feed consumption (RES) were recorded to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 22 publications
7
89
0
5
Order By: Relevance
“…Therefore, feeding coarse particles could result in conflicting effects on digestion efficiencies in growing chickens, depending on the nutrients and origin of feed particles. The genetic origin of birds was also shown to influence the effect of coarse particles, as reported by Rougière et al (2009) in a study using the genetic chicken lines D 1 and D 2 selected for divergent digestion efficiency (Mignon-Grasteau et al, 2004). According to Rougiè re et al (2009), coarse particles resulted in improved digestions of protein and energy in bad digesters (D 2 birds), whereas no effect was observed in good digesters (D 1 birds).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, feeding coarse particles could result in conflicting effects on digestion efficiencies in growing chickens, depending on the nutrients and origin of feed particles. The genetic origin of birds was also shown to influence the effect of coarse particles, as reported by Rougière et al (2009) in a study using the genetic chicken lines D 1 and D 2 selected for divergent digestion efficiency (Mignon-Grasteau et al, 2004). According to Rougiè re et al (2009), coarse particles resulted in improved digestions of protein and energy in bad digesters (D 2 birds), whereas no effect was observed in good digesters (D 1 birds).…”
Section: Introductionmentioning
confidence: 74%
“…This selection was conducted from 2002 at the Avian Research Unit (INRA, Nouzilly, France), on the basis of the apparent ME value of a wheat-based diet, corrected to zero nitrogen retention (AMEn), measured at 3 weeks of age (Mignon-Grasteau et al, 2004). The wheat samples of diets used for this genetic selection were all from the Rialto cultivar characterized by a very high viscosity of its water extract and a medium hard value.…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only very limited knowledge is available on the determinism of intra-specific variability in fiber digestibility in ruminants and pigs. A pioneer study has shown that the capacity of growing chicks to digest lowquality wheat is partially heritable and could be improved by selection (Mignon-Grasteau et al, 2004). Thus, a research priority is the development of breeding program for improving the digestive capacity of individuals (Issue 1: I1).…”
Section: Exploiting Animal Adaptive Capacitiesmentioning
confidence: 99%
“…Correlations between this and other performance traits, such as body weight (BW) gain and FCR were either low or negligible; suggesting that selection for P bioavailability will not affect adversely the performance (Zhang et al, 2003). The attempts of Carré et al (2008;Mignon-Grasteau et al, 2004;Pé ron et al, 2006) to select for overall digestive efficiency in broiler chickens have been more promising, as they reported relatively high heritabilities (0.33 to 0.47) for energy, lipid, starch and protein digestion efficiencies for 3-week-old broilers fed on a wheat-based diet in birds selected for digestive efficiency (Mignon-Grasteau et al, 2004). Interestingly, these differences had disappeared by 8 weeks of age and were affected greatly by diet type (Pé ron et al, 2006;Carré et al, 2008).…”
Section: Poultrymentioning
confidence: 99%